2013
DOI: 10.1073/pnas.1209078110
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 modulates oxidative stress induced cell death through suppression of apoptosis signal-regulating kinase 1

Abstract: Notch1 genes encode receptors for a signaling pathway that regulates various aspects of cell growth and differentiation; however, the role of Notch1 signaling in p38 mitogen-activated protein kinase (MAPK) signaling pathway is still not well defined. In this study, we found that Notch1 intracellular domain (Notch1-IC) prevents oxidative stress-induced cell death through the suppression of the Apoptosis signal-regulating kinase (ASK) 1 signaling pathway. Notch1-IC inhibited H 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Yang et al reported that the protective effects of curcumin against oxidative stress injury (OSI) are, at least in part, dependent on Notch1 inhibition . However, it is known that, high levels of exogenous ROS upregulate Notch1 [69] which is a potent inhibitor of the oxidative stress‐induced cell death signaling pathway, resulting in positively regulation of cell survival .…”
Section: Crosstalk Between Notch and Rosmentioning
confidence: 99%
“…Yang et al reported that the protective effects of curcumin against oxidative stress injury (OSI) are, at least in part, dependent on Notch1 inhibition . However, it is known that, high levels of exogenous ROS upregulate Notch1 [69] which is a potent inhibitor of the oxidative stress‐induced cell death signaling pathway, resulting in positively regulation of cell survival .…”
Section: Crosstalk Between Notch and Rosmentioning
confidence: 99%
“… 50 Notch1 signaling is induced by oxidative stress and Notch1 suppresses oxidative stress-induced cell death. 51 , 52 …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the expression of NOTCH1 was higher in those embryos exposed to OS coupled with elevated NFE2L2 transcript, as previously has been shown (Zhao et al, ). The upregulation of NOTCH1 under high oxygen level is attributed to cell apoptosis prevention via suppression of apoptosis signal‐regulating kinase 1 ( ASK1 ), and then preventing the p38 mitogen‐activated protein kinases signaling pathway (Mo et al, ). This was more pronounced in embryos produced in vitro (Heras et al, ).…”
Section: Discussionmentioning
confidence: 99%